Peran Notaris dalam Melegalisasi Dokumen Publik Asing Setelah Adanya Aksesi Konvensi Apostille - Nadira Aisyah Nurannisa (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This research is about the role of notaries in legalizing foreign public documents after accession to the Apostille convention through Presidential Regulation Number 2 of 2021. Legalization is the authority of notaries as regulated by the Law on the Position of Notaries. However, something new has emerged, namely regulations regarding the legalization of public documents that will be used abroad, including public documents by notaries, namely the legalization of Apostille. This type of research is empirical normative research carried out using a statutory and conceptual approach and prepared using primary legal materials in the form of laws and secondary legal materials, namely conducting interviews. The data obtained was processed in a quantitative descriptive manner. The results of this research explain that the role of the notary in legalizing public documents in the Apostille is under the authority of the Notary Position Law and Presidential Regulation Number 2 of 2021, the role of the notary is to register public documents via the online website of the Ministry of Law. and Human Rights. Then the legal certainty of the Apostille document's boundaries is not yet clear, only those outlined in Presidential Regulation Number 2 of 2021.